Kosmetik Halal dan Preferensi Gen Z: Studi Tentang Determinan dan Peran Gender - Afrina Riza Trinanda; Anita Priantina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the factors influencing the purchase intention of halal-labeled cosmetics among Gen Z and explores the moderating role of demographic variables. Using a quantitative approach and a case study design, data were collected from Gen Z consumers in Java through an online questionnaire and analyzed using the Structural Equation Modeling (SEM) method with SmartPLS 4.0. The findings indicate that religiosity and attitude have a significant and positive impact on purchase intention, while knowledge does not have a significant effect. Gender was found to moderate the relationship between religiosity and purchase intention, with religiosity having a stronger influence on women than on men. These results suggest that marketing strategies should emphasize religiosity and foster a positive attitude toward halal cosmetics, with a stronger focus on female consumers. Future research should expand the sample beyond Java and incorporate qualitative methods to explore additional factors influencing Gen Z's purchase intention of halal cosmetics.